2015
DOI: 10.1111/puar.12346
|View full text |Cite
|
Sign up to set email alerts
|

PAR’s Social Equity Footprint

Abstract: During the 75th anniversary of Public Administration Review (PAR), this article examines the social equity scholarship published in PAR from 1940 to 2013. Less than 5 percent of all articles published in PAR since its inception focus on social equity. The articles published in PAR are primarily concentrated within the areas of personnel and public policy. Very few articles were published in the areas of budgeting or ethics. While social equity scholarship published in PAR has made a valuable contribution to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 123 publications
1
100
0
Order By: Relevance
“…Dating back to Adams's () seminal work on motivation, organizational behaviorists have consistently found that inequity in wages and compensation among employees has harmful effects for morale and results in a variety of problems related to job satisfaction, turnover, and overall performance (Cho and Sai ; Choi ; Hassan ). Despite the enactment of legislation such as the Equal Pay Act of 1963 and the Lilly Ledbetter Fair Pay Act of 2009, female workers in many fields continue to face hurdles in securing equal pay in the workplace (Gooden ; Guy and Fenley ; Riccucci ). The 2014 median annual income of full‐time working women was only 79 percent that of full‐time working men (AAUW ).…”
mentioning
confidence: 99%
“…Dating back to Adams's () seminal work on motivation, organizational behaviorists have consistently found that inequity in wages and compensation among employees has harmful effects for morale and results in a variety of problems related to job satisfaction, turnover, and overall performance (Cho and Sai ; Choi ; Hassan ). Despite the enactment of legislation such as the Equal Pay Act of 1963 and the Lilly Ledbetter Fair Pay Act of 2009, female workers in many fields continue to face hurdles in securing equal pay in the workplace (Gooden ; Guy and Fenley ; Riccucci ). The 2014 median annual income of full‐time working women was only 79 percent that of full‐time working men (AAUW ).…”
mentioning
confidence: 99%
“…are efficiency and effectiveness values, not equity, fairness, or communal values" (82). NPM's focus on efficiency in this way stands in sharp contrast to the New Public Administration of the 1970s, in which social equity was the core value (Box 2015;Frederickson 2005b;Gooden 2015). While the dominance of NPM appears to have waned in public administration scholarship and practice, it remains a core value in newer paradigms as well.…”
Section: Did Efficiency Become a Primary Value In Public Management?mentioning
confidence: 99%
“…As scholars and practitioners, we have a duty to the discipline to unravel the causes and consequences for the persistence of discrimination in the workplace. Indeed, less than 5 percent of all articles published in Public Administration Review since its inception focus on social equity—which includes even less work on discrimination (Gooden ). Clearly, we need to do more.…”
Section: Making a Differencementioning
confidence: 99%